A study on the veneer recovery rate in a plywood plant / W. Mohd Nazri W. Abdul Rahman and Mohd Ariff Jamaludin - W. Abdul Rahman, W. Mohd Nazri; Jamaludin, Mohd Ariff (Universiti Teknologi MARA Cawangan Pahang, 2002)
A research to determine the recovery rate of logs that was to be converted into plywood was done at a local factory in Kuala Terengganu, Terengganu. The objectives of the research was to determine the effect of species, diameter and log shape on the recovery rate of veneer and to evaluate the volume of residue's losses in five early stages of the veneer production line. The five stages of veneer preparation studied were logyard/deck, debarker, rotary lathe, dryer and core builder/composer. The wood species studied were Meranti (Shorea spp.), Gerutu (Parashorea spp.), Kapur (Dyrobalanops spp.) and Simpoh (Dillienia spp.). These species were the most frequently used species in the factory. From the research, it was concluded that the recovery rate of Meranti was 58.38% (Shorea spp.), Gerutu was 58.31% (Parashorea spp.), Kapur was 60.34% (Dyrobalanops spp.) and Simpoh was 52.35% (Dillienia spp.). The analysis of the results showed that there was a significant difference in recovery rate between species. On the other hand, the recovery rate of logs with a diameter above 50 cm was 58.81% and diameter below 50 cm was 55.98 percent. The difference as observed in the analysis was not significant. The research also showed that the recovery rate for log shape factor for straight logs were 62.83% and curved logs were 51.96 percent. This showed that the log shape factor significantly affected recovery rate. The result of residue losses during the five main processes indicated that logyard/deck and debarker had a residue losses of 0.58-2.40%, rotary had 13.6914.90%, dryer had 4.72-8.49% and core builder/composer had 13.91-22.44 percent. It could be concluded that species and log shape factor contributed significantly towards the veneer recovery rate. Lastly, it could also be concluded that the core builder/composer section contributed to the highest residue losses.